Orange Roll Jelly Processing Training as a business opportunity in Tegalweru Village, Malang Regency - Norma Hasanatul Magfiroh Magfiroh; Elly Susanti (Journal of Community Engagement, 2025)
Tegalweru Village is one of the citrus producing centers in Malang Regency, but has no innovation in processing crops that have an impact on community economic empowerment. This study aims to assess the effectiveness of orange roll jelly processing training as a form of business opportunity based on local potential. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, documentation, and community empowerment. The training, which was held on January 19, 2023, was attended by 30 PKK mothers. The results showed an increase in participants' understanding of the manufacturing process and the business potential of the product. Orange roll jelly products are considered attractive, healthy because they are without preservatives, and have economic value. This training opens up opportunities for the formation of new MSMEs based on local potential and strengthens the empowerment of village women.